Synthesis, in vitro and in vivo evaluation of 18F-fluoronorimatinib as radiotracer for Imatinib-sensitive gastrointestinal stromal tumors - Prause, Martin; Niedermoser, Sabrina; Wängler, Carmen; Seibold, Uwe; Riester, Stephanie; Fricker, Gert; Wängler, Björn (Nuclear medicine and biology, 2018)
Introduction: Gastrointestinal stromal tumors (GIST) have a wide range of mutations, but can mostly be treated with Imatinib, until eventually resistance towards this tyrosine kinase inhibitor is acquired. Early and non-invasive determination of the sensitivity of the tumor and its metastases towards Imatinib by positron emission tomography (PET) would be beneficial for therapy planning and monitoring. Methods: We developed a synthesis strategy towards the precursor molecule, performed the 18F-synthesis and in the following evaluated the radioligand in vitro regarding its lipophilicity, stability and biological activity (KIT binding properties) as well as its in vivo properties in GIST tumor-bearing mice. Results: [18F]fluoronorimatinib could be obtained in an overall radiochemical yield of 22.2±3.3% within 90min. The radioligand showed high GIST cell uptake and was able to distinguish between Imatinib-sensitive and resistant tumor cell lines (GIST-T1, GIST882, GIST430) in vitro. Further biological evaluations of the ligand towards 9 different GIST-relevant KIT mutations showed comparable binding affinities compared to the structural lead Norimatinib (65nM vs. 53nM for wt-KIT). The in vivo evaluation of the newly developed radioligand showed tumor-to-background-ratios comparable to previously described, similar radiotracers. Conclusions: Thus, [18F]fluoronorimatinib is able to distinguish between Imatinib-resistant and sensitive KIT mutations. Although no improvement of in vivo tumor-to-background ratios could be achieved compared to formerly described radioligands, the hepatic uptake could be considerably reduced, being advantageous for the imaging of GIST. Advances in knowledge and implications for patient care: We were able to show that it is possible to significantly reduce the unfavorably high hepatic uptake of small-molecule radioligands applicable for GIST PET imaging. This work can thus be the basis for further work intending to develop a PET-radioligand for Imatinib-dependent GIST imaging.